PENGUATAN PENGETAHUAN DASAR AI UNTUK SISWA SMA DALAM KONTEKS PEMECAHAN MASALAH - Magfira, Fortia; Zuleriwati A.S; Manik , Agustina Sartika Yos Ekaristi; Pertiwi , Marisha; Silaban , Yessy Christanti (ASOSIASI IDEBAHASA KEPRI, 2025)
The development of Artificial Intelligence (AI) technology is rapidly advancing and has been applied across various fields, including education. However, high school students' understanding of AI remains limited. To address this, a community service activity in the form of an Inspiration Class was held at SMA Islam De Green Camp Tanjungpinang on June 4, 2025. This activity aimed to introduce the basic concepts of AI and its application in solving everyday problems. The activity employed an educational and participatory method, including interactive presentations, discussions, Q&A sessions, and simple simulations. The session was delivered by lecturers from Universitas Maritim Raja Ali Haji (UMRAH) and attended by 51 students. The material covered the definition of AI, examples of its implementation, and its role in modern life particularly in education, healthcare, and the environment. The results showed that students were enthusiastic and actively engaged in discussions. They began to understand the basic concepts of AI and how the technology can be used as a tool for problem-solving. This activity successfully sparked interest, curiosity, and critical thinking among students regarding technological developments.